Developing a Health Marketing Model to Foster a Culture of Timely Prostate Cancer Prevention - Sahafi, Elham; Hasanqolipour Yasuri, Tahmoores; Hosseini, Jalil; Shams, Ali (Archives of Men's Health, 2023)
Introduction: Prostate cancer poses a significant global public health concern for men. Despite advancements in medical knowledge and screening techniques, a considerable number of prostate cancer cases are diagnosed at advanced stages, leading to compromised treatment outcomes and increased mortality rates. This study aimed to develop and introduce a model focused on preventing prostate cancer in men. Methods: This mixed-methods study comprises two phases. In the initial phase, grounded theory was employed to identify and define the influential factors based on the prospectives of both experts and patients. The data were continuously analyzed during data collection using the Strauss & Corbin method (1998) encompassing open, axial, and selective coding. Subsequently, a systematic review and a qualitative study were conducted and the data were integrated to develop a cohesive model. Results: In the qualitative phase, axial coding yielded three axial subcategories: “Underlying factors”, “Causal conditions”, and “Intervening factors”. All extracted categories and codes were linked to the causal, background, intervention factors, strategies, and consequences adopting an approach focused on fostering a culture of timely prostate cancer prevention. A systematic review generated a final scale of 23 questions organized into four subscales: “Life conditions”, “Physical problems”, “Mental injuries”, and “Efficiency of hospitals” developed by the researcher in the second step. All steps of validity and reliability were undertaken. Following the integration of results from the systematic review and qualitative study (phases 1 and 2), the current research model measures the relationships between several latent variables (the primary variables of the research). Simultaneously, structural equation modeling was employed to analyze the data and test the hypotheses. Conclusion: The developed study model is validated and reliable, encompassing all the factors influencing prostate cancer prevention in men. Tailored to our context, this model was developed to prevent prostate cancer in men. Further testing in diverse societies is recommended.